Interpreting Clifford Geertz : Cultural Investigation in the Social Sciences - Alexander, Jeffrey C., 1947-; Smith, Philip (Philip Daniel), 1964-; Norton, Matthew, 1976-; Brooks, Peter, 1938- (New York: Palgrave Macmillan, 2011)
"Meaning is everywhere and everybody must interpret. Nobody argued this more persuasively than Clifford Geertz. From Balinese cock fights to sheep raids to theater states, Geertz showed that there is no escape from the sticky webs of meaning that capture our lives. But what exactly is Geertz saying, and should we still listen to him? After all, many argue that his ideas have run out of steam. This book confronts Geertz and his critics, offering surprising answers from various disciplines and identifying for the first time the contours of "the Geertz Effect.""--Provided by publisher.
Includes bibliographical references and index.
Keywords: Geertz, Clifford; Culture -- Research; Anthropology -- Research; Social sciences -- Research -- Methodology